Prevalence of Gastrointestinal Parasitic Infections in Cattle of Mahakaushal Region of Madhya Pradesh, India - Das, Giridhari; Kumbhakar, N.K.; Verma, Rupesh; Lata, Kusum; Saiyam, Rupanjali (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
Gastrointestinal (GI) parasitic infection in cattle is a worldwide problem as a cause of reduced productivity and profitability. The present study deals with the prevalence of various GI parasitic infections in cattle in the Mahakaushal region of Madhya Pradesh. A total of 1243 faecal samples collected during a period of one year revealed, 249 (20.03%) were positive for one or more gastrointestinal parasitic infection viz., Amphistomes (13.03%), Strongyle (5.47%), Moniezia (1.37%), Coccidia (1.21%), Fasciola (0.48%) and Toxocaravitulorum (0.16%) infection. Coproculture studies reveled that Haemonchus was predominant nematode followed by Oesophagostomum, Trichostrongylus, Strongyloides and Bunostomum. Seasonal prevalence revealed significantly higher (p < 0.01) prevalencein monsoon season (25.91%) than summer (21.40%) and winter (12.50%). Whereas, age wise prevalence was non-significantly higher in adult compared to young calves.
Keywords: Cattle; Gastrointestinal parasites; Prevalence; Madhya Pradesh